Recent Insights on the Maternal Microbiota: Impact on Pregnancy Outcomes - Di Simone, Nicoletta; Santamaria Ortiz, Amparo; Specchia, Monia; Tersigni, Chiara; Villa, Paola; Gasbarrini, Antonio; Scambia, Giovanni; D’Ippolito, Silvia (Frontiers in Immunology, 2020)
Hormonal changes during and after pregnancy are linked with modifications in the maternal microbiota. We describe the importance of the maternal microbiota in pregnancy and examine whether changes in maternal microbiotic composition at different body sites (gut, vagina, endometrium) are associated with pregnancy complications. We analyze the likely interactions between microbiota and the immune system. During pregnancy, the gastrointestinal (gut) microbiota undergoes profound changes that lead to an increase in lactic acid–producing bacteria and a reduction in butyrate-producing bacteria. The meaning of such changes needs clarification. Additionally, several studies have indicated a possible involvement of the maternal gut microbiota in autoimmune and lifelong diseases. The human vagina has its own microbiota, and changes in vaginal microbiota are related to several pregnancy-related complications. Recent studies show reduced lactobacilli, increased bacterial diversity, and low vaginal levels of beta-defensin 2 in women with preterm births. In contrast, early and healthy pregnancies are characterized by low diversity and low numbers of bacterial communities dominated by Lactobacillus. These observations suggest that early vaginal cultures that show an absence of Lactobacillus and polymicrobial vaginal colonization are risk factors for preterm birth. The endometrium is not a sterile site. Resident endometrial microbiota has only been defined recently. However, questions remain regarding the main components of the endometrial microbiota and their impact on the reproductive tract concerning both fertility and pregnancy outcomes. A classification based on endometrial bacterial patterns could help develop a microbiota-based diagnosis as well as personalized therapies for the prevention of obstetric complications and personalized treatments through nutritional, microbiotic, or pharmaceutical interventions.